Weeding regime and plant spacing influence on weed growth and performance of transplant aman rice variety Binadhan- 7 - Khan, Md Zonaed Kabir; Hasan, Ahmed Khairul; Anwar, Md Parvez; Islam, Md Shahadul (Fundamental and Applied Agriculture, 2017)
Plant spacing and weeding regime are amongst the key factors determining rice growth and yield through maximum utilization of space, plant nutrients, water and sunlight. Therefore, it is essential to identify optimum spacing and proper weeding regime for ensuring the potential yield of a rice cultivar. A field experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University (BAU), Mymensingh during July- December 2012 to study the influence of spacing and weeding regime on the performance of transplant aman rice cv. Binadhan-7. The experiment comprised four plant spacings viz. 25 cm × 15 cm, 20 cm × 15 cm, 15 cm × 15 cm and 15 cm × 10 cm, and five weeding regimes viz. no weeding, one weeding at 15 days after transplanting (DAT), two weeding at 15 and 30 DAT, three weeding at 15, 30 and 45 DAT and weed free. The experiment was laid out in a randomized complete block design (RCBD) with three replications. The highest weed density and dry weight were recorded with the spacing of 20 cm × 15 cm and 25 cm × 15 cm, respectively. But the lowest values were observed in the closest spacing of 15 cm × 10 cm. Plant spacing exerted significant influence on most of the plant characters except plant height and 1000- grain weight. The highest and statistically significant grain yield was obtained from 20 cm × 15 cm spacing (6.05 t ha-1) and 25 cm × 15 cm spacing (6.04 t ha-1) because of highest number of filled grains panicle-1 (143.65) and highest number of effective tillers hill-1 (10.13). Weeding regime also had significant effect on all the parameters except 1000-grain weight. The highest grain yield (6.29 t ha- 1) was obtained from the weed free condition which produced 37.33% higher yield than unweeded condition (4.58 t ha-1). Interaction between plant spacing and weeding regime significantly influenced all the parameters studied except 1000- grain weight. The highest grain yield (6.71 t ha-1) was obtained from the interaction between 20 cm x 15 cm spacing and three weeding regimes at 15, 30, 45 DAT which was similar to the treatment combination of 15 cm × 15 cm spacing and weed free condition. But maintaining season long weed free condition is not practical from economic view point, therefore Binadhan-7 should be transplanted at 20 cm × 15 cm spacing following three times weeding at 15, 30 and 45 DAT for higher yield and effective weed control.